Exosomes overexpressing miR-34c inhibit malignant behavior and reverse the radioresistance of nasopharyngeal carcinoma - Fang-Zhu Wan (Journal of Translational Medicine, 2020)
Abstract Background Malignant behavior and radioresistance, which severely limits the efficacy of radiation therapy (RT) in nasopharyngeal carcinoma (NPC), are associated with tumor progression and poor prognosis. Mesenchymal stem cells (MSCs) are used as a therapeutic tool in a variety of tumors. The aim of this study was to reveal the effect of tumor suppressor microRNA-34c-5p (miR-34c) on NPC development and radioresistance, as well as to confirm that exosomes derived from MSCs overexpressing miR-34c restore the sensitivity to radiotherapy in NPCs. Methods Potentially active microRNAs were screened by cell sequencing, Gene Expression Omnibus (GEO) database analysis, and analysis of clinical serum samples from 70 patients. The expression of genes and proteins was detected by Western blotting, quantitative reverse transcription PCR (qRT-PCR), and immunohistochemistry (IHC). Proliferation, apoptosis, invasion, migration and radioresistance of NPC were detected. Luciferase reporter assays were used to verify the interactions of microRNAs with their downstream targets. MSCs exosomes were isolated by ultrafiltration and verified by electron microscopy and nanoparticle tracking technology. Results The expression of miR-34c was associated with the occurrence and radiation resistance of NPC. In vitro and in vivo experiments indicated that overexpression of miR-34c inhibit malignant behavior such as invasion, migration, proliferation and epithelial-mesenchymal transition (EMT) in NPCs by targeting β-Catenin. In addition, we found alleviated radioresistance upon miR-34c overexpression or β-catenin knockdown in NPCs. Exosomes derived from miR-34c-transfected MSCs attenuated NPC invasion, migration, proliferation and EMT. Moreover, miR-34c-overexpressing exosomes drastically increased radiation-induced apoptosis in NPC cells. Conclusion miR-34c is a tumor suppressor miR in NPC, which inhibits malignant behavior as well as radioresistance of tumor. Therefore, exogenous delivery of miR-34c to NPCs via MSC exosomes inhibits tumor progression and increases the efficiency of RT. Combination IR with miR-34c-overexpressing exosomes may be effective treatment for radioresistant NPCs.